Comedy Content Creation of COVID-19 Awareness on @arditerwandha's Social Media Platform - Adinda Berliani; Anathasia Citra (Expose: Jurnal Ilmu Komunikasi, 2022)
To spread awareness about Coronavirus disease (COVID-19), content creators create social media content. Ardit Erwandha, a stand-up comedian, is one of the creators who uses humor in Social Media Content (SMC) about the Coronavirus. This study aims to understand why Ardit Erwanda used comedy in his SMC related to COVID-19 and the process he does to create the content. Furthermore, this study utilizes humorous communication theory because this theory explains the function of Humor (comedy) beyond its common understanding as an entertainment source. This qualitative research uses the Interpretivism paradigm and utilizes a case study. In addition, the researchers use in-depth interview as a primary data-collecting technique and collects literature reviews for discussion materials. The results of this study indicate that the humor approach in Ardit's SMC is used to convey criticism, relieve anxiety, and ease tension while representing people's feelings in terms of relatability. Ardit Erwanda goes through the following stages when creating content: goal setting, audience mapping, content ideas and planning, content creation, content distribution, content amplification, content evaluation, and content improvement.